ASME/STLE 2007 International Joint Tribology Conference, Parts a and B 2007
DOI: 10.1115/ijtc2007-44485
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Boundary Lubricating Additives on DLC Coatings

Abstract: The friction properties of a range of boundary lubricating additives in DLC-DLC sliding-rolling, lubricated contact have been investigated. Two types of DLC have been studied, one hydrogenated diamond-like and the other a non-hydrogenated graphitic type. The graphitic-type DLC coating gave initially very low boundary friction with additive-free base oil but after a few minutes of rubbing in thin film conditions this rose to the higher value produced immediately by the diamond-like DLC. With the graphitic-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 0 publications
3
25
0
1
Order By: Relevance
“…boundary friction increasing with mean speed; Figure ) with gear oils 2, 4 and 5 is an indication of the formation of an effective film, derived possibly from organic FM present in these gear oils. Such low‐speed low‐friction behaviour is attributed to adsorbed films from FM as reported in a similar study by Topolovec‐Miklozic et al ., Ingram et al . and Campen et al .…”
Section: Discussionsupporting
confidence: 80%
“…boundary friction increasing with mean speed; Figure ) with gear oils 2, 4 and 5 is an indication of the formation of an effective film, derived possibly from organic FM present in these gear oils. Such low‐speed low‐friction behaviour is attributed to adsorbed films from FM as reported in a similar study by Topolovec‐Miklozic et al ., Ingram et al . and Campen et al .…”
Section: Discussionsupporting
confidence: 80%
“…The absence of any formed tribolm on non-doped H-DLC was reported extensively in the literature, [37][38][39][40][41][42] whereas other studies found that some thin tribolms can be formed. [43][44][45][46][47][48][49] The formation and composition of such lms will be investigated further using the in situ surface analysis of XANES P and S kedges, which is discussed in detail in the subsequent sections.…”
Section: Friction and Wear Performancementioning
confidence: 99%
“…Since the molecular chemistry of the ionic liquid additive in both lubricant mixtures is identical, better tribological behaviour was contributed to the higher concentration, and hence, higher reserve of the additive, which can form durable protective film. This mechanism was already adopted for the certain group of the friction modifiers, [36][37][38][39][40] and it was proven in our previous work. 19 The additional data that confirm the better performance of the protective film generated from the C8-ImIL/I mixture are gained from the ECR measurements ( Figure 7).…”
Section: Discussionmentioning
confidence: 99%